Republic of Belarus : Technical Assistance Report-Work of Mission on Development of Potential in Area of Government Finance Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
In consultation with the Republic of Belarus Ministry of Finance (MoF), a government finance statistics (GFS) technical assistance (TA) mission from the IMF's Statistics Department (STA) visited Minsk from November 13 through 24, 2017. The main objective of the mission was to take stock of the progress in government finance statistics in the Republic of Belarus and to provide assistance to the MoF in improving the quality of statistical data. Government finance statistics provide a comprehensive conceptual and accounting framework suitable for the analysis and evaluation of fiscal policy, and in particular the performance of the general government sector of any country. One of the biggest advantages of the introduction of GFS methodology into budgeting is the achievement of consistency in budgeting, financial reporting, and statistics. Use of the same terminology by those engaged in budgeting, reporting, and statistics should ensure common understanding among all of the stakeholders. The comparability of numbers, tables, and accounts is significantly enhanced, which means an improvement in productivity and in the timely availability of data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet